Pelatihan dan Pendampingan Model SCL (Student Center Learning) Berbasis Lesson Study Content Learning Loss di SDN 005 Tarakan - Kartini, Kartini; Wahid, Sucahyo Mas’an Al; Andari, Kadek Dewi Wahyuni; Pratiwi, Enditiyas; Noer, Roby Zulkarnain; Agustina, Degi Alrinda; Ramdhan, Donna (Universitas Nusantara PGRI Kediri, 2022)
The learner-centred learning model (SCL) has been released by the government with a variety of syntax examples at every level of education and provides enough space for modification, innovation and creativity, but not many schools have done it. Regarding the lack of training in the application of the student center learning learning model, which causes the lack of planning as outlined in the lesson plans in schools so that there is no clear reflection that is suitable for implementation in elementary schools in the city of Tarakan. The method of implementing the activities is carried out online and for the implementation of Lesson Study, activities are carried out offline but only in a smaller capacity. The targets and targets in these problems are as follows: 1) Brainstorming the application of the SCL model; 2) Assistance in making online-based plans, do, see; 3) Monitoring and evaluation of Learning Loss; 4) Formation of WhatsApp Groups with SCL Model content in schools. The results found during the service, namely: 1) Training on the application of learning models needs to be studied considering the development of science and how to get information; 2) The readiness of the participants to take part in the workshop is quite good; 3) Some of the participants were actively consulted via WhatsApp Groups; 4) Participants are able to work on assignments according to the specified time starting from identifying the SCL model to applying it according to offline and online learning media.